Multifunctional Nanomaterials for Energy Applications - Cesano, Federico; Rackauskas, Simas; Uddin, Mohammed (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The rapid growth of the world's population has significantly increased energy consumption and environmental impact. The transition from fossil fuels to sustainable energy sources that is needed for a sustainable future demands more efficient materials and improved technologies, but allows us to tackle this great and necessary challenge. This Special Issue highlights some of the latest energy advances in the field of materials, in particular low-dimensional materials, and nanostructured materials. Various topics related to synthesis and characterization methods, properties, and energy application uses are highlighted.